FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN MEMBAYAR OUT OF POCKET PASIEN ASURANSI DI INSTALASI RAWAT JALAN POLI PENYAKIT DALAM RSU KOTA TANGERANG SELATAN TAHUN 2019 - Farah Elena Astrilia (2020)
Health is a basic human need that can be achieved through various efforts including health service. The government established a national health insurance program (NHI) to increase access to health services but the program is still not optimal, it affects the number of hospital visits and income. Therefore it required an analysis of insurance patient's willingness to pay out of pocket for outpatient services. The purpose of this study is to determined the insurance patient's willingness to pay out of pocket and their correlation with patient's income, distance to hospital, treatment experience, information, ability to pay (ATP), health services, and health insurance. This research is a cross sectional study on 124 respondents using a questionnaire. Data were analyzed using chi square and logistic regression. The results outcomes shows that the level of willingness to pay of respondents is quite high and is influenced by patient's income (p value = 0.001), information (p value = 0.045), treatment experience (p value = 0.010), and ability to pay (ATP) (p value = 0.001). Factors that have the most significant associations were patient's ability to pay (OR= 14,502). In conclusion, patient's income, information, treatment experience, and ATP affect the willingness to pay of patients.